(untitled) (Psychology Travelogs, 2025)
The article is devoted to a critical analysis of the traditional approach to understanding intelligence, which for a long time was regarded as a single cognitive ability measurable quantitatively through IQ tests. The authors examine contemporary scientific perspectives that demonstrate human intelligence as a complex, multidimensional system comprising independent yet interconnected cognitive functions. Special attention is given to the comparison between human and artificial intelligence: the article analyzes how neuroscientific research confirms the presence of consciousness, emotionality, moral judgment, and reflection in humans, which fundamentally distinguishes them from algorithmic models. The authors emphasize that the unitary concept of intelligence fails to account for the neuropsychological specialization of distinct cognitive functions such as language, logical reasoning, social interaction, spatial perception, and emotional regulation, each possessing its own mechanisms of development and activation. The analysis presented demonstrates that reducing intelligence to a single numerical indicator is scientifically unfounded, as it does not reflect the complexity of the brain’s cognitive architecture. The role of artificial intelligence is considered separately, focusing on its ability to perform highly specialized tasks and the limitations of algorithmic modeling of thought processes. Despite significant technological advances, the authors highlight that AI cannot replicate introspection, moral motivation, or the social context of decision-making, underscoring the uniqueness of human thinking. The authors propose expanding neuroscientific studies on the mechanisms of cognitive activity and analyzing the interplay between social factors and intellectual development.